Lipoic acid biosynthesis defects. Issue 4 (29th April 2014) - Mayr, Johannes A.; Feichtinger, René G.; Tort, Frederic; Ribes, Antonia; Sperl, Wolfgang
Abstract: Lipoate is a covalently bound cofactor essential for five redox reactions in humans: in four 2‐oxoacid dehydrogenases and the glycine cleavage system (GCS). Two enzymes are from the energy metabolism, α‐ketoglutarate dehydrogenase and pyruvate dehydrogenase; and three are from the amino acid metabolism, branched‐chain ketoacid dehydrogenase, 2‐oxoadipate dehydrogenase, and the GCS. All these enzymes consist of multiple subunits and share a similar architecture. Lipoate synthesis in mitochondria involves mitochondrial fatty acid synthesis up to octanoyl‐acyl‐carrier protein; and three lipoate‐specific steps, including octanoic acid transfer to glycine cleavage H protein by lipoyl(octanoyl) transferase 2 (putative) (LIPT2), lipoate synthesis by lipoic acid synthetase (LIAS), and lipoate transfer by lipoyltransferase 1 (LIPT1), which is necessary to lipoylate the E2 subunits of the 2‐oxoacid dehydrogenases. The reduced form dihydrolipoate is reactivated by dihydrolipoyl dehydrogenase (DLD). Mutations in LIAS have been identified that result in a variant form of nonketotic hyperglycinemia with early‐onset convulsions combined with a defect in mitochondrial energy metabolism with encephalopathy and cardiomyopathy. LIPT1 deficiency spares the GCS, and resulted in a combined 2‐oxoacid dehydrogenase deficiency and early death in one patient and in a less severely affected individual with a Leigh‐like phenotype. As LIAS is an iron–sulphur‐cluster‐dependent enzyme, a number of recently identified defects in mitochondrial iron–sulphur cluster synthesis, including NFU1, BOLA3, IBA57, GLRX5 presented with deficiency of LIAS and a LIAS ‐like phenotype. As in DLD deficiency, a broader clinical spectrum can be anticipated for lipoate synthesis defects depending on which of the affected enzymes is most rate limiting.